Design and Performance Test of Measuring Apparatus of Dielectric Properties Using Q-Meter Method - Armansyah H. Tambunan; Nugroho A. Suyanto; . Harmen (PERTETA, 2000)
Dielectric heating has received a lot of attention recently. Microwave heating, however, has the problem of noticeable hot and cold spots within a food. Radio frequency (RF) has the potential to overcome this problem because of its longer wavelength and greater penetration depth, which would lead to more uniform distribution of the electric field and thus a more uniform temperature distribution. The dielectric properties are the measure of a sample's response to an electromagnetic field, which vary significantly with frequency, temperature, moisture, and salt content. The potential of a medium to respond to dielectric heating can be characterized by its dielectric properties, which can be strong functions of frequency and temperature. This experiment is aimed to design and test the performance of a measurement apparatus for the dielectric properties, using the Q-meter method.